Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Moderasi Beragama Siswa Kelas VII Sekolah Menengah Pertama Negeri 07 Bontang Tahun Pembelajaran 2022/2023 - Munir, Misbahul; Sesar, M. (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This article discusses the Efforts of Islamic Religious Education Teachers in Increasing Religious Moderation of Class VII Students of State Junior High School 07 Bontang. This study aims to determine how the efforts of Islamic religious education teachers in increasing religious moderation of grade VII students of State Junior High School 07. Religious moderation is the creation of tolerance, mutual respect and respect between religions with one another. The purpose of this study is how the efforts of Islamic religious education teachers in increasing religious moderation at Sekolah Menengah Junior Negeri 07 Bontang. Whether the efforts of Islamic religious education teachers can increase religious moderation at Sekolah Menengah Junior Negeri 07 Bontang. This research was conducted through a qualitative approach. Where researchers go directly to the field to find out the phenomena that occur, in accordance with the problem formulation that has been prepared. Data collection that researchers do through interviews, observations, and documentation using data analysis, data presentation and conclusions. From the results of the study can be concluded as follows: Teachers' efforts in increasing religious moderation for students are indirect learning, direct learning and habituation in religious moderation for students. The efforts of Islamic religious education teachers can improve such as establishing cooperation and getting full support by school principals, parents and teachers. While the inhibiting factor is the lack of facilities in religious moderation.